Research on factors affecting the satisfaction of companies using accounting services in Vietnam - Yen Thi Tran; Trang Huyen Thi Phan; Chung Thi Phan (My University, 2023)
Research on factors affecting the satisfaction of companies using accounting services in Vietnam
Keywords: Accounting services; Company satisfaction; Vietnam